Supporting School Resilience: A Study on a Sample of Teachers after the 2016/2017 Seismic Events in Central Italy - Anna Salerni; Alessandro Vaccarelli (LED Edizioni Universitarie, 2019)
Between 2016 and 2017, a series of high-intensity earthquakes devastated Central Italy, with great repercussions on the lives of people and local communities. The article reports the results of a research concerning the impact of the catastrophe on the school world, on the teaching profession and on the behavior of the students. Special attention was paid to teachers' resilient skills and their professional responses in catastrophic situations. For the survey, we used a questionnaire and a test for the study of resilience, administered to a sample of 477 teachers from Lazio and Abruzzo. The results showed that the experience of the catastrophe has a significant influence on teaching professionalism, professional motivation, levels of resilience and behaviors observed in the students. In the light of the results, it is possible to state that in emergency situations teacher training on help relationship and resilience becomes a crucial factor in supporting their professionalism, with important repercussions on students and on school organization.